The Change of CulturalMemory on an Iconic Structure: Narmanlı Han - Sav, Sedef (My University, 2018)
Narmanh Han1 is one of the most important iconic historic structure with its intangible dimensions in the memory of the city. According to its distinctive history, it could be observed that the building was used as a centre for culture and art due to its significant settlers. Since 2015, there was a renewal project has been going on in spite of the public’s concern. To understand this renewal project better, similar recent renewal projects in Beyoğlu has been analysed in this study. Additionally, according to theoretical background, texts and regulations such as FARO Convention, Recommendation on the Historic Urban Landscape, the Burra Charter and the Charter of Krakow were analysed to underline both tangible and intangible dimensions of the cultural heritages. In consideration of the interviews with the old users of Narmanh Han, study aims to clarify the intangible dimensions of the building.
Keywords: Narmanh Han; Heritage Preservation; Intangible Dimension; Cultural Memory